2007
DOI: 10.1016/j.semcancer.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory costimulation and anti-tumor immunity

Abstract: Costimulation was originally shown to be important in T-cell activation and effector differentiation. Recent characterization of B7/butyrophilin and members of the CD28 superfamily has revealed a large number of negative costimulatory molecules that dampen T-cell activation and regulate immune tolerance. Some of these molecules have been shown to be upregulated in the tumor microenvironment and may serve as potential targets for augmenting anti-tumor immunity. In this article, we summarize recent developments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…Moreover, human BTN2A1 has been shown to modulate immature dendritic cells (DC) by binding to Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN) [41], and Btnl1 has been recently found to regulate interactions with intraepithelial γδT lymphocytes in the murine small intestine by suppressing pro-inflammatory mediators of the NFκB pathway, such as IL-6, IL-15, CXCL1, and CCL4 [42]. In addition, many members of the B7-homolog (B7-H) family, such as PD-1 and CTLA-4, are expressed on tumour cells in various cancers, where they can be exploited by the cancerous cells to escape from immune destruction and impede B7 ongoing immune processes [43,44]. The presence of the deletion and the subsequent absence or reduced expression of the encoded proteins would allow a stronger response against tumour cells, implying that the BTNL8_BTNL3-del allele could act as a positive modulator of anti-tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, human BTN2A1 has been shown to modulate immature dendritic cells (DC) by binding to Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN) [41], and Btnl1 has been recently found to regulate interactions with intraepithelial γδT lymphocytes in the murine small intestine by suppressing pro-inflammatory mediators of the NFκB pathway, such as IL-6, IL-15, CXCL1, and CCL4 [42]. In addition, many members of the B7-homolog (B7-H) family, such as PD-1 and CTLA-4, are expressed on tumour cells in various cancers, where they can be exploited by the cancerous cells to escape from immune destruction and impede B7 ongoing immune processes [43,44]. The presence of the deletion and the subsequent absence or reduced expression of the encoded proteins would allow a stronger response against tumour cells, implying that the BTNL8_BTNL3-del allele could act as a positive modulator of anti-tumour immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The extended B7 family also include ICOS ligand (ICOSL, also known as B7h, ICOS-L, B7RP-1, and B7-H2), B7-H1(also known as PD-L1, B7-H, CD274), B7-H2 (also known as PD-L2 and B7-DC), B7-H3 (also known as CD276 and B7RP-2), and B7-H4 (also known as VTCN1, B7X, and B7S1). They play variable roles in maintaining the intricate cellular network of the tumor immune suppressive microenvironment [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…T cell activation is regulated simultaneously by positive and negative signals, in part but importantly via the interaction of costimulatory molecules between receptors on T cells and their ligands on APCs (1)(2)(3). In addition to CD28 and ICOS, which provide positive costimulation to enhance T cell activation, numerous inhibitory ligands or receptors have been identified that regulate immune tolerance and/or the magnitude of T cell immune responses.…”
mentioning
confidence: 99%